Review of Nikos Demertzis, Eleni Paschaloudi and Giorgos Antoniou (eds), Εμφύλιος: Πολιτισμικό τραύμα [Civil war: cultural trauma] - Dalkavoukis, Vasilis (Historein, 2014)
Nikos Demertzis, Eleni Paschaloudi and Giorgos Antoniou (eds), Εμφύλιος: Πολιτισμικό τραύμα [Civil war: cultural trauma], Athens: Alexandria, 2013. 351 pp.